2018
DOI: 10.1007/s11356-018-2887-0
|View full text |Cite
|
Sign up to set email alerts
|

A cost compensation model for construction and demolition waste disposal in South China

Abstract: Construction and demolition waste (C&D waste) is a worldwide issue that concerns the sustainable development of the construction industry. In this paper, detailed formulas are listed for calculating the costs of four typical kinds of disposal routes of C&D waste. They are illegal dumping, controlled dumping (landfill), centralized recycling, and on-site recycling. Through the specific formulas, the costs of the new construction project in Guangzhou are also estimated. Then, a cost compensation model of constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 40 publications
0
11
0
2
Order By: Relevance
“…The result differs from Shurrab et al (2019). One possible explanation is that in most developing countries, price competition strategies are still dominant in the construction sector, meaning projects or practices with lower costs get selected or adopted more often than green projects or GPs (Liu, Teng, Jiang, & Gong, 2019). Likewise, in developing countries, environmental goals are considered less important than the national development agenda of providing the people infrastructure, housing and services needs, which explains insufficient support for GPs (Ma, Hou, & Xin, 2017;Yusof & Kamal, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…The result differs from Shurrab et al (2019). One possible explanation is that in most developing countries, price competition strategies are still dominant in the construction sector, meaning projects or practices with lower costs get selected or adopted more often than green projects or GPs (Liu, Teng, Jiang, & Gong, 2019). Likewise, in developing countries, environmental goals are considered less important than the national development agenda of providing the people infrastructure, housing and services needs, which explains insufficient support for GPs (Ma, Hou, & Xin, 2017;Yusof & Kamal, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…Ajayi and Oyedele (2017) explored the policy directions for C&D waste minimization in the UK. Liu, Teng, Jiang, and Gong (2018) suggested several policy proposals for promoting C&D waste reuse and recycling in Guangzhou. Besides, a number of studies claimed the important role of government in effective C&D waste management (Duan, Li, & Liu, 2017; Liu, Nie, & Yuan, 2020; Udawatta et al, 2018; Wu, Zuo, Zillante, Wang, & Yuan, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To use a value of WTA from the literature is seldom possible; on the contrary, a different value should be used for different municipalities, since social factors significantly influence the value in question [61]. Numerous other case studies can be found in the literature; herein we refer to [62][63][64][65][66][67].…”
Section: Discussionmentioning
confidence: 99%